Cavernous haemangioma of maxillary sinus: a camouflaged presentation - Santiyamadhi, S.; Komathi, R.; Mohamad, Noraini; Tang, Ing Ping (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Cavernous haemangioma of the nose and paranasal sinuses is a rare lesion which often misdiagnosed preoperatively. It is slow growing and locally destructive due to pressure effect thus simulating the features of a malignant lesion. In this case we presented a 64-year-old gentleman whom presented with bleeding from right alveolar ridge. On examination revealed a friable mass of 2×2 cm which bled on contact mimicking malignant lesion. CT scan revealed a heterogenously enhancing soft tissue lesion with surrounding bone remodelling which made it difficult to rule out malignancy. The tissue punch biopsy suggestive of inflammatory myofibroblastic tumour, however unable to rule out low grade malignancy. With the dilemma of making an accurate preoperative diagnosis, we proceeded with right total maxillectomy as to provide a total resection of the tumour. Postoperative histopathological examination confirmed to be cavernous haemangioma. This camouflaged presentation of cavernous haemangioma was a challenge in the decision making to provide the best curative treatment. Cavernous haemangioma of maxillary sinus is a complex entity, thus diagnosing this lesion is in grey area for the surgeons. A high index of suspicion combined with the radiological finding is crucial in deciding the treatment option in such camouflaged presentations. An analytical and suspicious mind combined with histopathological and radiological examination is pertinent for confirmation of the diagnosis.